1995
DOI: 10.1007/s001250050359
|View full text |Cite
|
Sign up to set email alerts
|

Variation by age group and seasonally at diagnosis of childhood IDDM in Europe

Abstract: Recent data provided by the EURODIAB ACE study group have confirmed wide variation in the incidence of insulin-dependent diabetes mellitus (IDDM) across Europe. The aim of this report is to compare age-specific incidence and seasonality at clinical onset of IDDM between study regions. Using a uniform methodology, the EURODIAB ACE framework ascertained 3,168 newly-diagnosed cases of IDDM in children under the age of 15 years during 1989-1990. Eighteen percent of the cases were age 0-4 years at diagnosis, 34% we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
61
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 26 publications
23
61
1
Order By: Relevance
“…The same network has also established age-group differences in incidence rate by geographical region [4]. This study shows that no differences in the proportion of children presenting with ketoacidosis could be observed between age groups but that differences existed between geographical regions with higher rates of diabetic ketoacidosis found in regions with lower incidence rates.…”
Section: Discussionmentioning
confidence: 66%
“…The same network has also established age-group differences in incidence rate by geographical region [4]. This study shows that no differences in the proportion of children presenting with ketoacidosis could be observed between age groups but that differences existed between geographical regions with higher rates of diabetic ketoacidosis found in regions with lower incidence rates.…”
Section: Discussionmentioning
confidence: 66%
“…Seasonal patterns of onset of type 1 diabetes have been found, with incidence peaking in the winter months (1)(2)(3)5) and in both sexes during puberty (3). In contrast, other studies have found no seasonal differences in the month of onset in girls (8).…”
Section: Introductionmentioning
confidence: 95%
“…Seasonal variations in glycated haemoglobin (HbA1c) at follow-up have been observed in adults and children with type 1 diabetes, with the lowest values during the summer and the highest levels during the winter (1)(2)(3)(4)(5). Some studies have found the greatest seasonal variations in older age groups (4), but no gender differences have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Early introduction of cows' milk proteins, short duration of breastfeeding, rapid growth or weight gain, puberty, pregnancy, obesity, vitamin D deficiency, cold climate, psychological stress, maternal blood group incompatibility, dietary toxins and viral infections have all been proposed to initiate or promote diabetes, but none has emerged so far as the prime aetiological factor [2,6,7,8,9]. Several epidemiological studies have described a seasonal pattern in the onset of juvenile diabetes, with a peak incidence in winter and a nadir in the warmer summer months [10,11,12,13]. This seasonal variation has been taken as an indirect argument in favour of the role of environmental factors, such as viral infections or cold climate, in the development of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…This seasonal variation has been taken as an indirect argument in favour of the role of environmental factors, such as viral infections or cold climate, in the development of the disease. Studies by EURODIAB (Europe and Diabetes) in patients diagnosed under age 15 have shown heterogeneity in the seasonal pattern of clinical onset according to age at diagnosis and region [10,13]. However, most cases of Type 1 diabetes are diagnosed in people over the age of 15 [1,14].…”
Section: Introductionmentioning
confidence: 99%